Risk Factors for Work-related Musculoskeletal Disorders among Sugar Factory Workers in Jinja, Eastern Uganda: A Cross-Sectional Study - Aremu Abdulmujeeb Babatunde; Owino Alfred Odongo; Ismail Bamidele Afolabi; Joseph Juma; Suleiman Mbaruk Abdalla (The Indonesian Journal of Occupational Safety and Health, 2023)
Introduction: The disease outcome of musculoskeletal disorders includes; serious occupational disorders and disabilities that are associated with the loss of useful working days and socioeconomic burden to the individual, the organization, and society at large. The aim of this study is to determine the work-related musculoskeletal disorders and associated risk factors among sugar factory workers. Methods: The cross-sectional study design was employed in this study in the workplace among 402 workers between two sugar factories. The self-structured Standardized Nordic Musculoskeletal Disorders questionnaire was administered. Data were analysed into descriptive statistics, binary logistic, and multiple logistic regression using SPSS vs. 26. Results: The results indicate that the prevalence of work-related musculoskeletal disorders in the previous 12 months among sugar factory workers was 53%. The Lower back region has the highest prevalence of 52.2% and the lowest prevalence of 12.7% on Neck region. The following highlighted factors were significantly associated with the reporting of WRMSD among sugar factory workers during the last 12-months, such as; age of the respondents, educational status, work designation, monotonous task, standing for long periods, and time taken to carry out the task. Conclusions: Workers in sugar factories are constantly exposed to ergonomic hazards which predisposed them to WRMSD. If these situations are not prevented it might worsen the burden of WRMSDs among workers, result in cases of more absenteeism and low productivity.